Peningkatan Perkembangan Motorik Halus Anak Usia4-5 Tahun Melalui Kegiatan Melipat Kertas Di TkDiponegoro Asam Jawa Kecamatan TorgambaKabupaten Labuhanbatu Selatan - Netti Herawati Netti Herawati; Bukhari Iskandar; Suryatik; Soybatul Aslamiah Ritonga (Jurnal Zeniusi, 2024)
The basis for this study is the observation that children's fine motor abilities at TK Diponegoro Asam Jawa, Torgamba District, South Labuhanbatu Regency, have not grown to their full potential. Nearly 80% of students need help from the teacher to finish learning activities like paper weaving, which are designed to improve fine motor skills. Children find the methods less engaging because they are not the best, and thematerial does not align with the studied issues. This study aims to ascertain whether paper folding exercises at TK Diponegoro Asam Jawa have improved the fine motor skills of children ages 4-5. This study employs a descriptive methodology. This studyuses documentation and observation as data collection methods. Children from TK Diponegoro Asam Jawa's Group A are the study's subjects. According to the study's findings, 34 youngsters (100%) attended cycles I and II. Of 34 pupils, 11.76% demonstrated Very Good Development (BSB) in cycle I and 29.41% in cycle II. BSH, or development according to expectations, was 23.53% in cycle I and 50% in cycle II. Beginning to Develop (MB) was 23.53% in cycle I and 20.59%in cycle II. Not Developing (BB) was 0% in cycle II and 41.18% in cycle I. As a result, cycle II classifies it as complete